1991
DOI: 10.1111/j.1549-0831.1991.tb00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Exports, Food Production, and Food Security in Latin America1

Abstract: This study assesses the impact of agricultural, export-oriented policies on food consumption through a time-series, cross-sectional regression model. The results of this study lead to three basic conclusions.First, there is a significant negative relationship between agricultural export promotion and food consumption. Economic growth and increasing agricultural exports earnings do not necessarily increase food security. Second, protein consumption per capita constitutes a more sensitive indicator of changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Three early studies based on country-level data found a negative association between dependence on non-service or primary exports and average per capita availability of calories and especially proteins in the Latin-American context [60] and for developing countries in general [61, 62]. This negative relationship was attributed partly to the restrictions to imports including quotas and other non-tariff barriers that frequently accompanied export-promotion policies [60]. These studies, however, found the impacts to be small compared to the effects of foreign investment [61] or insignificant after controlling for investment and other economic variables [62].…”
Section: Resultsmentioning
confidence: 99%
“…Three early studies based on country-level data found a negative association between dependence on non-service or primary exports and average per capita availability of calories and especially proteins in the Latin-American context [60] and for developing countries in general [61, 62]. This negative relationship was attributed partly to the restrictions to imports including quotas and other non-tariff barriers that frequently accompanied export-promotion policies [60]. These studies, however, found the impacts to be small compared to the effects of foreign investment [61] or insignificant after controlling for investment and other economic variables [62].…”
Section: Resultsmentioning
confidence: 99%
“…5 These have been an important outlet for sociological analysis (see Babbie 1982;Barrett and Greif 2008;Boardman, Saint Onge, Rogers and Denney 2005;Buttel 2000;Cereseto 1977;de Janvry 1976;Friedmann 1993;Gacitua and Bello 1991). The International Journal of Sociology of Agriculture of Food from the International Sociological Association's Research Committee on Food and Agriculture is one specific source that has been an abundant source of sociological research.…”
Section: Endnotesmentioning
confidence: 99%
“…Among other economic problems was the ineffective marketing system in Africa and other developing countries (Meissner 1989;Gacitua and Bello 1991;Cheng 1989). The World Food Conference of 1976 considered ineffective marketing, and especially lack of capital, in the developing countries as a central problem; other factors include the lack of coordination in production, lack of infrastructure, excessive waste in food distribution, and lack of adequate agricultural practices.…”
Section: Gross National Product (Gnp) Often Is Used As An Indicationmentioning
confidence: 99%
“…A commonly used empirical measure of food shortage, which is the dependent variable in the theoretical hypotheses, is calorie intake (Wimberley 1990), in part because it is considered to be a good indicator of other nutrients (Gacitua and Bello 1991).…”
Section: Dependent Variablesmentioning
confidence: 99%